Envisioning the Future of Extension and Advisory Services in the Caribbean - Wayne G. Ganpat; Amy Harder; Austen Moore (Journal of International Agricultural and Extension Education, 2014)
Recent efforts have begun to renew collaborative relationships between actors leading extension systems throughout the Caribbean Community. Successful collaborations are built upon a shared vision. This study was conducted to determine the degree to which a shared future vision for extension and advisory services (EAS) existed within CARICOM countries. A qualitative approach was used to investigate the perceptions of EAS directors from nine CARICOM countries. Similar concerns about the future relevance of EAS were expressed. More diversity existed when considering primary stakeholders and delivery methods. The formal adoption of a shared vision for the region and creation of supportive policies are recommended
Keywords: Vision; CARICOM; Extension; Caribbean; Relevance